Regulating the Unregulated: The Advent of Fintech Regulations and Their Impacts on Equity-Based Crowdfunding - M. Aydemir; A. F. Aysan (BRICS Law Journal)
The concept of equity-based crowdfunding (ECF) has become one of the latest innovative financing alternatives for startups and SMEs throughout the world during the last decade. This article aims to assess the revised crowdfunding directive of Turkey and its role in the development of the ecosystem. The concept of ECF is elucidated with its stakeholders, challenges, and solutions. Then the effect of the revised regulation is analyzed through a case study of the first active ECF platform in Turkey, Fonbulucu. Finally, the article discusses the potential improvements to the existing directive considering the practices of Fonbulucu.